Anthropocène, apocalypse et parousie ? - Dominique Bourg (Socio-anthropologie, 2013)
What do we mean by “Anthropocene”? This text seeks first to clarify the meaning of this expression and show how it places humanity in the long term, in contrast to previous findings and analysis on the fragility of the planet. Yet the Anthropocene does not exclude the possibility of an apocalyptic horizon. Instead, two scenarios may indeed give two different images of the future of the Anthropocene. The first is that humanity seems at first to neglect the limits of the planet to succumb at the end, dramatically. In the second, collapse after collapse, it may be another humanity, having overcome his demons, which could happen.